Bromocriptine improves glucose tolerance in obese mice via central dopamine D2 receptor-independent mechanism - Hiroshi Tsuneki; Takahiro Maeda; Mayumi Takatsuki; Takahiro Sekine; Satsuki Masui; Kengo Onishi; Ryuta Takeda; Masanori Sugiyama; Takeshi Sakurai; Masashi Yanagisawa; Tsutomu Wada; Toshiyasu Sasaoka (PLoS ONE, 2025)
Bromocriptine, generally regarded as a dopamine D2 receptor agonist, has been used to treat patients with type 2 diabetes in the USA; however, its mechanisms of action including the receptors that mediate its anti-diabetic effects remain unclear. Therefore, we herein conducted pharmacological and genetic knockout experiments to investigate how bromocriptine improves glucose metabolism under type 2 diabetic conditions. Bromocriptine transiently increased blood glucose levels in both wild-type and dopamine D2 receptor-deficient mice. This glucose-elevating effect was blocked by the α2-adrenergic receptor antagonist yohimbine. On the other hand, when bromocriptine was administered daily for two weeks, glucose tolerance improved in wild-type mice fed a high-fat diet. Similar anti-diabetic effects of bromocriptine were observed in dopamine D2 receptor-deficient, dopamine D1 receptor-deficient, and orexin-deficient mice under the diet-induced obese condition as well as in genetically obese db/db mice. Bromocriptine-induced improvements in glucose tolerance were not affected by a pretreatment with the autonomic ganglion blocker hexamethonium, which suggested the involvement of the peripheral effects of bromocriptine. Given the biphasic properties of bromocriptine, we examined the drug effect on hepatic endoplasmic reticulum (ER) stress that dually regulates glucose metabolism. In the livers of diet-induced obese mice, the levels of ER stress markers, including C/EBP homologous protein (CHOP), were reduced by the daily administration of bromocriptine. In human hepatoma HepG2 cells, increases in CHOP expression by thapsigargin, a potent inducer of ER stress, were prevented by a pretreatment with low concentrations of bromocriptine, whereas high concentrations induced CHOP expression. These results suggest that low concentrations of bromocriptine caused beneficial ER stress preconditioning, which protected against subsequent severe ER stress in the liver. Therefore, bromocriptine may prevent obesity-induced glucose intolerance via peripheral mechanisms including promotion of hepatic ER homeostasis, but not central dopamine D2 receptor-mediated mechanisms.